2019
DOI: 10.4103/ijnmr.ijnmr_86_18
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cognitive behavioral therapy on the burden in drug dependent persons' caregivers: A randomized controlled clinical trial

Abstract: Background: Drug dependence is one of the current problems that leads to the drug dependents persons' suffer and imposes a huge mental burden to their family members. This study aimed investigating to determine the effect of cognitive- behavioral therapy (CBT) on the burden of the caregivers of drug dependent people. In CBT, caregivers discover thought and behavioral mistakes and recover them. Materials and Methods: This randomized controlled clinical trial was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Five of these trials reported improvements in the others’ affected psychological wellbeing for one or more of the reported outcomes. This related to anxiety [ 79 , 80 ], depression [ 81 ], self-esteem [ 82 ], coping [ 82 ], co-dependent behaviour [ 83 ], and partner enabling behaviour [ 80 ]; one trial reported a reduction in the burden of care for family members of drug users [ 84 ]. Conversely, no improvement was reported relating to anxiety in family members of alcohol users [ 81 ] or mental health problems in families of drug users [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five of these trials reported improvements in the others’ affected psychological wellbeing for one or more of the reported outcomes. This related to anxiety [ 79 , 80 ], depression [ 81 ], self-esteem [ 82 ], coping [ 82 ], co-dependent behaviour [ 83 ], and partner enabling behaviour [ 80 ]; one trial reported a reduction in the burden of care for family members of drug users [ 84 ]. Conversely, no improvement was reported relating to anxiety in family members of alcohol users [ 81 ] or mental health problems in families of drug users [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…Family caregivers in this population might benefit from increased organizational support and evidence-based interventions designed by healthcare professionals to foster resilience and coping. Using cognitive behavior therapy as an intervention effectively reduced caregiver burden associated with OUD in a randomized controlled trial in Iran (Faghih & Pahlavanzadeh, 2019). Programs that offer resiliency training such as the Mastery, Openness to experience, Reflective attitude, and Emotional regulation (MORE) wisdom training have also shown some benefit with family caregivers; however, more research is still needed (Kim & Knight, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Significant caregiver burden can result in socioeconomic deprivation from expenditures on healthcare treatment and rehabilitation, legal fees, and lost wages (Biegel et al, 2010; Cicek et al, 2015). Caregivers to this population with OUD also have increased difficulty coping and problem solving related to a range of economic and legal problems, social isolation, poor physical health, psychiatric illness, and violence (Cosentino et al, 2017; Faghih & Pahlavanzadeh, 2019; Maina et al, 2021). Recent research findings also indicate caregivers of individuals with SUD experience a lower quality of life and have higher family stigma (Rohit et al, 2019).…”
mentioning
confidence: 99%
“…Este mismo hallazgo lo reportaron Ruiz-Robledillo y Moya-Albiol (2015) en un estudio no experimental en el que se utilizaron técnicas de estrategias de afrontamiento centradas en problemas y de relajación. Además, las intervenciones cognitivo conductuales han mostrado ser un tratamiento efectivo para disminuir la sobrecarga percibida en muestras de cuidadores de personas con diversas afectaciones (Faghih & Pahlavanzadeh, 2019;Mosley et al, 2021;Rosas-Santiago et al, 2018.…”
Section: Estimación Intragrupal Del Efecto De La Intervenciónunclassified